Three-dimensional modeling and geostatistical structural analysis for ore deposit prospecting trend and wisdom mining: a case study in the Jiaoxibei gold field, China - Liu, Xiaoning; Wang, Gongwen; Lv, Jingyi; Peng, Yongming; Zhao, Xianyong (Frontiers in Earth Science, 2024)
The orientation of deep-seated orebodies was observed shifted from northwest to north at the Xincheng deposit in the Jiaoxibei gold field during the mining operations. To make informed decisions, understanding the geological factors influencing this directional change is crucial for mining engineers. Prior research suggested the ore-controlling fault morphology might correlate with the orebody positions and the thickness of alteration zones. Hence, the morphology of fault structures emerges is a key point in this work. Firstly, we constructed a three-dimensional (3D) fault surface model. A large fault framework was interpreted using gravity-magnetic-electrical geophysical datasets, then the local details of the fault surfaces were characterized using an interpolation method based on drillhole fault gouge data. Subsequently, we statistically assessed the spatial association between fault morphology and orebodies positioning by standardized C-values method, and demarcated the ore-controlling structures on fault surfaces using quantitative indicators.The indicators of fault dips, fault azimuths, and the second-order trend residuals of fault surfaces represented the fault morphology. The drillhole grade data (Σsampling grade * sampling length) was used to describe the scale of mineralization zones, and the cumulative thickness of the pyrite-sericite altered rocks indicated the intensity of alteration zones. Finally, geostatistical structural analysis was employed to depict the mineralization orientation at different locations. Through these methods, we aim to propose a potential pattern of how ore-controlling fault morphology spatially influences the positions and orientations of orebodies. This comprehensive approach offers valuable insights into exploring deep-seated mineralization at the Xincheng deposit, aiding in a better understanding of the deposit's geological dynamics for future mining endeavors.